Emerging Approaches to Profile Accessible Chromatin from Formalin-Fixed Paraffin-Embedded Sections - Vishnu Udayakumaran Nair Sunitha Kumary; Bryan J. Venters; Karthikeyan Raman; Sagnik Sen; Pierre-Olivier Estève; Martis W. Cowles; Michael-Christopher Keogh; Sriharsa Pradhan (Epigenomes, 2024)
Nucleosomes are non-uniformly distributed across eukaryotic genomes, with stretches of ‘open’ chromatin strongly associated with transcriptionally active promoters and enhancers. Understanding chromatin accessibility patterns in normal tissue and how they are altered in pathologies can provide critical insights to development and disease. With the advent of high-throughput sequencing, a variety of strategies have been devised to identify open regions across the genome, including DNase-seq, MNase-seq, FAIRE-seq, ATAC-seq, and NicE-seq. However, the broad application of such methods to FFPE (formalin-fixed paraffin-embedded) tissues has been curtailed by the major technical challenges imposed by highly fixed and often damaged genomic material. Here, we review the most common approaches for mapping open chromatin regions, recent optimizations to overcome the challenges of working with FFPE tissue, and a brief overview of a typical data pipeline with analysis considerations.